2014
DOI: 10.1016/j.apsusc.2014.02.124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, Hall effect and THz conductivity of epitaxial thin films of Fe chalcogenide superconductors

Abstract: Method of synthesis of high-quality thin films of Fe chalcogenides, Fe(Te,Se) and FeSe are studied. By investigating the correlation between Tc and structural parameters, it is concluded that a compressive strain is introduced on the films on CaF2 substrate, which leads to an increase of Tc than on oxide substrates. Properties both in the normal state and in the superconducting state are measured. Results are discussed in terms of the possibility of further increasing Tc of this material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Data from literature are added for comparison; in these cases, the critical temperature is the one declared in the original papers. The data come from PCARS [3], STS [4,6,10], ARPES [2,9], tunnel spectroscopy [5], specific heat [35] and THz spectroscopy [32].…”
Section: Resultsmentioning
confidence: 99%
“…Data from literature are added for comparison; in these cases, the critical temperature is the one declared in the original papers. The data come from PCARS [3], STS [4,6,10], ARPES [2,9], tunnel spectroscopy [5], specific heat [35] and THz spectroscopy [32].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in R H may be related to the nematicity in FeSe. [28][29][30] In contrast, it has been reported that the sign of R H for FeSe single crystals is negative at low temperatures. 31,32) The origin of the difference in R H can be explained by the difference in the band structures between single crystals and films on CaF 2 .…”
mentioning
confidence: 91%
“…The complete phase diagram that we present provides a novel perspective for the mechanism of superconductivity of this material. The data for x = 0 and 0.5 presented in (a)-(e) are cited from our previous papers [4,14].…”
mentioning
confidence: 99%